The Influence of The Work Environment on Employee Work Productivity PERUMDA Air Minum Tirta Medal Sumedang Utara - Anggini, Megah Dewi; Damayanti, Wulan Ariani; Jaja, Jaja (Journal of Bussines Management Basic, 2024)
An organization's expansion and improvement are inextricably bound up with its physical setting. Put another way, the company's productivity is only one indicator of how the work environment impacts the business. The key to a company's success or failure is its productivity, hence measuring it is crucial. North Sumedang Tirta Medal Water Company has also suffered a drop in output, which is attributable, in part, to staff carelessness but also to factors like an unpleasant workplace and inadequate illumination. The purpose of this research is to ascertain the extent to which the working conditions of the Perumda Water Drinking Tirta Medal, North Sumedang personnel affect their output on the job. Approach Quantitative methodologies were used in this investigation. The data is presented in this paper. This follows the rules of quantitative research, which use data collection, processing, and interpretation in statistical hypothesis testing to explain the connection between variables. This research found that for n = 28 (df=26), the t-value is 3.032, with a p-value of 0.05. The results show that the X-variable (Work Environment) influences the Y-variable (Work Productivity) according to these standards (tcount ttable = 3.032, 2.05553).